Marcação-soltura-recaptura para determinar o tamanho da população natural de Anopheles albitarsis l.s. (Diptera: Culicidae) Marking-release-recapture methods for determining the size of the natural population of Anopheles albitarsis l.s. (Diptera: Culicidae) - Roseli La Corte dos Santos; Oswaldo Paulo Forattini (Universidade de São Paulo, 1999)
OBJETIVO: Objetivou-se estimar o tamanho de população natural de Anopheles albitarsis s.l. presente em fazenda de plantação com arroz irrigado no Vale do Ribeira, SP, Brasil, no período do verão, como subsídio para avaliação da capacidade vetora. MÉTODOS: Foram feitos três experimentos de marcação-soltura-recaptura com pó fluorescente, com populações de campo e populações criadas em laboratório. Foram realizadas, concomitantemente, capturas com isca humana. RESULTADOS: A população estimada em três eventos de soltura foi 64.560, 50.503 e 22.684 mosquitos. A taxa de picadas/homem/noite variou entre 41,5 e 524,5. CONCLUSÃO: Observou-se alta densidade de mosquitos no período considerado, permitindo inferir que, ainda que a sobrevivência da espécie seja baixa, número substancial de fêmeas pode sobreviver tempo suficiente para ultrapassar o período extrínseco de desenvolvimento do parasita. OBJECTIVE: In order to evaluate the size of the Anopheles albitarsis s.l. population in the Ribeira Valley region of the south-eastern S. Paulo State, Brazil, marking-release-recapture experiments were carried out on the Experimental Farm in Pariquera-Açu county where an artificial irrigation system for the cultivation of rice has been installed. The experiments aimed at determining the vectorial capacity of this species. METHODS: During the summer (January, February and March), three marking-release-recapture experiments with field and laboratory reared populations were conducted to evaluate the population size. Simultaneous human bait collections were also carried out to estimate the human biting rate. RESULTS: The population sizes of the three experiments were estimated to be 64,560, 50,503 and 22,684 mosquitoes. The bite/man/night rate varied from 41.5 to 524,5. DISCUSSION: The results indicated high mosquito density in the summer which allow one to infer that, even though the survival rate is low, the number of remaining females is large enough to outlive the parasite's extrinsic developmental period.